Generation Development of Public Administration And the Future of Arab Government Administration: An Inductive Analysis of Challenges and Responses - Eldeqen, Ahmed (The Arab Journal of Administration, 2020)
This study aimed to uncover the challenges facing generations of public administration and analyze the responses of generations of public administration to the challenges they faced, and the scientific rooting for the third generation of modern public administration that could shape the future of the Arab government administration for better development performance. The study relied on the evolutionary approach and employed the theory of challenge and response in the context of inductive analysis. The study started from a major research question about: how public administration responded to the technological, economical challenges and social policies facing it. A sub-questions emerged from this main research question about: what are the technological, economical, political and social challenges, that faced the first generation of public administration and led to development to the second electronic/ economic generation, and what are the technological and economic challenges facing the second generation of modern public administration that lead to The third generation under the Fourth Industrial Revolution.